The Development of Contingency Theory in Public Sector: An Overview - Hadiyanti, Endang; Jannah, Lina Miftahul; Lutfi, Achmad (International Journal Labs, 2024)
The purpose of this study is to provide an overview of contingency theory research, particularly in the public sector. The inductive approach of a series of studies with the goal of theoretical development in the field of investigation served as the foundation for the research methodology and design. We focus on the publication in journals indexed on the Scopus database. A quantitative bibliometric analysis is carried out. 159 articles on the topic were located. We also identified the authors, journals, nations/regions, and the number of citations that contributed most to the growth of the investigation in this research topic by encouraging the analysis of strict bibliometric tools. To better understand the evaluation of the research topic, we use the VOSviewer software. As a result, despite a very slow start in 1979, this field of study has significantly expanded in recent years. There was a total of 13 documents published in 2019 and 2022, and so far in 2024, 9 documents have been published. With 44 documents published, the United States is the country or territory that has conducted most of this research; Indonesia is in sixth place with 9 documents.